INFLUENCE OF AUDITOR’S COMPETENCE, INDEPENDENCE, ACCOUNTABILITY, AND DUE PROFESSIONAL CARETO AUDIT QUALITY - Ulfa, Maria (Liability, 2019)
This study examines influence of competence, independence, accountability, and due professional care to audit quality. Respondents in this study are auditors who worked for Public Accounting Firm in Surabaya. The number of auditors that were visited in this study were 51 auditors from 8 Public Accountant Firms. The method of determining the sample is using purposive sampling method, auditor who have been experienced in auditing more than 5 year while the data processing method used in this research were four methods, method of analysis used in hypothesis testing is multiple regression which will declare link between independent variable to dependent variable. The result shows competence, independence, accountability, and due professional care simultaneously and significantly influence to audit quality. This significant link is positive that means if the independent variable increased then same goes to the dependent variable and in reverse.